Implementasi Metode Hypnoteaching dalam Meningkatkan Motivasi Belajar Santri Studi Kasus Pondok Pesantren An-Nuur Al-Fadhol Banyuwangi - Abdul Rokib; Muhammad Yusron Maulana El-Yunusi (LPPM STAI Ihyaul Ulum Gresik, 2023)
The Hypnoteaching method is to permanently and maximally increase students' learning motivation, due to the nature of the subconscious mind that stores a memory of one's mind starting from the womb since the spirit is blown until now. Thus raising a research title